PENGARUH PENGGUNAAN LIMBAH WORTEL (Daucus carota L.) DALAM RANSUM SAPI PERAH BERBASIS RUMPUT LAPANGAN TERHADAP FERMENTABILITAS DAN KECERNAAN (IN VITRO - Ai Neni Nurhayati; Iman Hernaman; Ujang Hidayat Tanuwiria; Ana Rochana Tarmidi (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2020)
Carrot waste grows in the highlands and has the potential to feed of dairy cows. The aim of this research is to utilize carrot waste in dairy cow ration and its impact on fermentability and digestibility in vitro. The study was conducted experimentally using a completely randomized design. Data were analyzed using variance analysis and Duncan's test. Analysis of the relationship between variables using correlation-regression analysis. The treatments (as fed) consist of: T0 = Concentrate + 100% Native Grass (Basal Ration), T1 = Concentrate + 50% Native Grass + 50% Carrot Leaves, T2 = Concentrate + 50% Native Grass + 25% Carrot Leaves + 25% Carrot Meal, T3 = Concentrate + 50% Native Grass + 50% Carrot Meal, each repeated 4 times. The results showed that the use of carrot waste did not affect ammonia production, but affected the production of flying fatty acids, dry matter digestibility and organic matter digestibility. Flying fatty acids, digestibility of dry matter, digestibility of organic matter is higher in rations using carrot waste compared to basic rations. The highest value of volatile fatty acids, dry matter digestibility and organic matter digestibility were obtained in the treatment of 50% carrot tuber replacing field grass (T3), which were 139.53 mM, 56.21% and 58.86%, respectively. Between the digestibility of dry matter and organic matter has a very close relationship with the regression equation y = 0.9135x + 7.3654 and a correlation value of r = 0.8814. The results of this study can be concluded that the use of carrot waste can increase the production of volatilr fatty acids, dry matter digestibility and organic matter with the use of carrot male by 50% (as fed) as a substitute for field grass gives the best results.